Evolution of symbiosis in hermatypic corals: A model of the past, present, and future. (December 2016) - Antonelli, Peter L.; Rutz, Solange F.; Sammarco, Paul W.; Strychar, Kevin B.
Abstract: This work can be considered a prequel to our previous paper on coral bleaching induced by global warming. We once again investigate, using Finsler geometry, dynamical energy budget theory and nonlinear modular mechanics, the origin of endosymbiosis, between reef-building corals and the algae. We assume their relationship starts out as entosymbiosis, with the algal organism living on the external surfaces of host coral exoskeleton, but with both gradually adapting to each other over evolutionary time-scales. Our main conclusion is that such an evolutionary conversion is possible and indeed is quite likely.